Critical zone 2 : a forum of Chinese and western knowledge - Tong, Q. S.; Wang, Shouren; Kerr, Douglas (Hong Kong University Press ; Nanjing University Press, 2007)
Despite globalizing forces, whether economic, political, or cultural, there remain conspicuous differences that divide scholarly communities. How should we understand and respond to those discursive gaps among different traditions and systems of knowledge production? Critical Zone is a book series in cultural and literary studies that is concerned with current critical debates and intellectual preoccupations in the humanities. The series aims to improve understanding across cultures, traditions, discourses, and disciplines, and to produce international critical knowledge. Critical Zone is an e.